3C.03: OPTIMAL DURATION OF HOME BLOOD PRESSURE MEASUREMENTS FOR THE DIAGNOSIS OF ARTERIAL HYPERTENSION. (June 2015) - Kim, J.; Lee, M.Y.; Kim, J.; Namgung, J.; Lee, S.Y.; Cho, D.K.; Choi, T.Y.; Kim, S.Y.; Park, J.; Park, S.M.
Abstract : Objective: The optimal measurements duration and cut off values for home blood pressure monitoring (HBPM) are not well defined for the first diagnosis of hypertension. In this study, we compare three measurement duration protocols (3 day, 5 day and 7day) of HBPM considering 24 h ambulatory blood pressure monitoring (ABPM) as a reference standard for the diagnosis of hypertension. Design and method: Two hundred and sixty six subjects who are suspected to have hypertension in office BP were completed to 24 h ABPM and to 7 days HBPM protocol from 4 university hospitals. HBPM protocol consists of three measurements taken 2 h in waking up (between 7:00 and 9:00 a.m.) and three measurements taken before sleep (between 9:00 and 11:00 p.m.) for 7 days. Hypertension was defined as BP more than 130/80 mmHg for ABPM. Results: The area under the ROC curve (95% confidence interval) was 0.801 (0.735–0.867) for the 3-day measurements, 0.787 (0.719–0.856) for the 5-day measurements, and 0.789 (0.720–0.859) for the 7-day measurements for the diagnosis of hypertension. There were no significant difference of intraclass correlation coefficients of systolic and diastolic blood pressure between measurement duration protocols and ABPM. Bland–Altman plots showed smaller and random dispersion for the 3-day HBPM measurements. Optimal cut off values of 3 day HBPM measurements by Youden index were 132.1 mmHg in systolic BP (sensitivity: 70% and specificity: 72%) and 81.8 mmHg in diastolic BP (sensitivity: 88% and specificity: 59%). Conclusions: A 3-day protocol of HBPM has not inferior accuracy than a 5-day and 7-day measurement of HBMP for the diagnosis of hypertension considering ABPM as a reference. Optimal BP threshold values of the 3 day HBPM protocol are lower than HBPM values of current guideline (135/85mmHg).